A tale of two properties : debt strategies for financing commercial real estate - Furfine, Craig (London : Kellogg School of Management, 2019)
Stanley Cirano owned two retail shopping centers in suburban Chicago. With interest rates near all-time lows in late 2015, Cirano believed it was an opportune time to consider the debt financing of his properties. Although the properties were similar in many respects, the lenders willing to lend against each property were offering noticeably different terms. Cirano had to consider not only the interest rate and size of each potential loan, but also the various fees, potential prepayment penalties, and variations in recourse to make the best decision for each property.
Originally Published InFurfine, C. (2019). A Tale of Two Properties: Debt Strategies for Financing Commercial Real Estate. 5-318-503. Evanston, IL: Kellogg School of Management, Northwestern University.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Commercial real estate -- United States -- Case studies; Commercial loans -- United States -- Case studies